Disenchanting citizenship : Mexican migrants and the boundaries of belonging - Plascencia, Luis F. B. (Latinidad., 2012)
Luis F.B. Plascencia's Disenchanting Citizenship explores two interrelated issues: U.S. citizenship and the Mexican migrants' position in the United States. Through an extensive and multifaceted collection of interviews, ethnographic fieldwork, ethno-historical research, and public policy analysis, Plascencia probes the ways in which citizenship discourses are understood and taken up by individuals. The book uncovers citizenship's root as a Janus-faced construct that encompasses a simultaneous process of inclusion and exclusion. This notion of citizenship is mapped on to t.